Phylogeny and Historical Biogeography of Paphiopedilum Pfitzer (Orchidaceae) Based on Nuclear and Plastid DNA - Tsai, Chi-Chu; Liao, Pei-Chun; Ko, Ya-Zhu; Chen, Chih-Hsiung; Chiang, Yu-Chung (Frontiers in Plant Science, 2020)
ABSTRACT The phylogeny and biogeography of the genus Paphiopedilum were evaluated by using phylogenetic trees derived from analysis of nuclear ribosomal ITS sequences, the plastid trnL intron, the trnL-F spacer, and the atpB-rbcL spacer. This genus was divided into three subgenera: Parvisepalum, Brachypetalum, and Paphiopedilum. Each of them is monophyletic with high bootstrap supports according to the highly resolved phylogenetic tree reconstructed by combined sequences. There are five sections within the subgenus Paphiopedilum, including Coryopedilum, Pardalopetalum, Cochlopetalum, Paphiopedilum, and Barbata. The subgenus Parvisepalum is phylogenetic basal, which suggesting that Parvisepalum is comprising more ancestral characters than other subgenera. The evolutionary trend of genus Paphiopedilum was deduced based on the maximum likelihood (ML) tree and Bayesian Evolutionary Analysis Sampling Trees (BEAST). Reconstruct Ancestral State in Phylogenies (RASP) analyses based on the combined sequence data. The biogeographic analysis indicates that Paphiopedilum species were firstly derived in Southern China and Southeast Asia, subsequently dispersed into the Southeast Asian archipelagoes. The subgenera Paphiopedilum was likely derived after these historical dispersals and vicariance events. Our research reveals the relevance of the differentiation of Paphiopedilum in Southeast Asia and geological history. Moreover, the biogeographic analysis explains that the significant evolutionary hotspots of these orchids in the Sundaland and Wallacea might be attributed to repeated migration and isolation events between the south-eastern Asia mainland and the Sunda Super Islands.